Selective inhibition of canonical STAT3 signaling suppresses K-ras mutant lung tumorigenesis and reinvigorates anti-tumor immunity - Clowers, Michael J.; Rahal, Zahraa; Cho, Sung-Nam; Krishna, Avantika; Yuan, Bo; Hamana Zorrilla, Leticia G.; Eckols, T. Kris; Kasembeli, Moses M.; Liu, Samuel; Peng, Stephen; Ramos-Castaneda, Marco; Thompson, Annamarie L.; et al. (Frontiers in Immunology, 2025)
IntroductionK-ras mutant lung adenocarcinoma (KM-LUAD) is a difficult-to-treat cancer subtype in which chronic inflammation pervades the tumor immune microenvironment (TIME). Pro-inflammatory pathways dampen the response to treatments, including immune checkpoint inhibitors, necessitating therapies that target this inflammatory signaling network in the TIME. One of the lynchpins of chronic inflammation in KM-LUAD is signal transducer and activator of transcription 3 (STAT3).MethodsHere, we tested the anti-tumor and early immunotherapeutic efficacy of TTI-101, a selective small-molecule inhibitor of canonical STAT3 signaling, in a K-rasG12D mutant lung cancer mouse model (CC-LR).ResultsTreatment of CC-LR mice with TTI-101 resulted in reduced tumor burden while increasing dendritic cell (DC) and T helper 1 (Th1) infiltration into the TIME. TTI-101 treatment decreased pY-STAT3 expression in tumors with accompanying increases in several NF-κB anti-tumor target genes including CXCL9, a chemokine for primed T cells. Transcriptional profiling of the TIME revealed improved immune activation and anti-tumor skewing, as well as B cell signaling enrichment. Analysis of human LUAD data demonstrated negative correlations between STAT3 and Th1/DC infiltration, with DC infiltration also conferring improved survival in LUAD patients with low STAT3.DiscussionOur results highlight the importance of STAT3 in driving early tumorigenesis and offer a preventative treatment window for high-risk individuals and patients with early-stage KM-LUAD.